L'interprete e il traduttore Saggi di Teoria della letteratura - Sabelli Biagini, Vincenzina (Moderna/Comparata, 2016)
What is a comment? What does it mean to interpret a text? What are the skills and methods used by great masters such as Auerbach, Spitzer, Sontag, Segre, Adelia Noferi, Contini, Barthes and Raimondi in their dialogue with the ancient and new hermeneutic theories? What kind of relationship is established between message/text and commentator? What is the common ground where the act of interpreting and that of translating end up meeting? Enza Biagini wonders about these fundamental questions while, between comment and commentary, she carries out an articulated and complex study on one of the major arts born for and around reading: translation. A demanding game is indeed played between interpreter and translator, which Enza Biagini analyses and discusses with great theoretical knowledge, crossing Italian and French experiments, original texts and anthologies, with the aim of verifying theories on the field of literature which, as such, is based on an endless quest for the interpretation of meaning.